Potrebe bolnic z rakom dojke po celostni rehabilitaciji - Potisek, Kristina (Medicinski razgledi, 2011)
Backgrounds. Breast cancer is the most frequent cancer among women in Slovenia. At the end of the treatement breast cancer patients encount problemson multiple areas of functioning, this is why they require a comprehensive rehabilitation process. The aim of our study was to explore problems encountered by breast cancer patients at different levels of tre atment and find out the factors that mostly influence their quality oflife. Methods. The first questionnaire was administered to female breast cancer patients, aged from 18 to 85, who underwent surgery from January 2009 to June 2009 in the Institute of Oncology, Ljubljana, the day before the surgery. Three months after surgery, questionnaires were readministered by postal mail.We us ed 3 different questionnaires. Analyses of results were performed including descriptive statistics and paired samples t-test. Results. Patients were from 31 to 83 years old. Two thirds of them had comorbidities. On average, preoperative problems were reported in 3 out of 11 areas for body functions, and 2 out of 11 involving activities and participation. Postoperatively, the number of problem s increased in both areas by 2, mosdy related to home activities. A significant decrease in functioning and quality oflife was observed after the treatment. Conclusions. Women with breast cancerhave prexisting problems with functioning prior to surgery. To prevent progression of these problems into chronic stage, a comprehensive rehabilitionduring the diagnostic stage is recommended, rather than only once treatment has commenced.
Keywords: Breast Neoplasms; Mastektomija; Kvaliteta življenja; Rehabilitation; Mastectomy; Dojka, novotvorbe; ankete; Quality Of Life; Questionnaires; dojka; novotvorbe; tumor; rak (medicina); rehabilitacija; vocational rehabilitation